Firm Characteristic, Islamic Corporate Social Responsibility, and Implementation of Environmental Management Accounting (EMA) - Afifah, Ni’mah Nur; Hadi, Nor; Citradewi, Adelina (IQTISHADIA, 2023)
This article aims to empirically examine the effect of industry sensitivity, public ownership, and Corporate Social Responsibility (CSR) on the implementation of Environmental Management Accounting (EMA). The three independent variables test the contingency theory in the form of a contingent or contextual variable relationship in encouraging the implementation of the EMA. This study uses secondary data to collect data using the documentation method in the annual report and sustainability report in 2021. The sample was determined using purposive sampling, consisting of 46 manufacturing firms in the basic and chemical industries, mining, and consumer goods industries registered at the Indonesia Stock Exchange (IDX). Data processing employs Ordinary Least Squares (OLS). The results showed that two of the three hypotheses were rejected, namely, industry sensitivity (H1 ) and public ownership (H2 ), indicating no effect on EMA, while Islamic Corporate Social Responsibility (ICSR) (H3 ) indicated an influence on EMA. The test results imply that contingencies considerations in the form of high-cost ICSR alignments and not necessarily recommendations in conventional accounting recognition encourage the implementation of EMA. It is necessary to determine the suitability of the contingency variables in encouraging the implementation of the EMA.